Introducing infant and young child feeding indicators into national nutrition surveillance systems: lessons from Vietnam. Issue 3 (18th September 2013) - Hajeebhoy, Nemat; Nguyen, Phuong Hong; Tran, Do Thanh; de Onis, Mercedes
Abstract: A comprehensive set of infant and young child feeding (IYCF) indicators for international use was published in 2008. We describe the process followed to incorporate these indicators into Vietnam's National Nutrition Surveillance System (NNSS). Following its establishment in 1980, the National Institute of Nutrition introduced the Vietnam NNSS to provide an evidence base for nutrition interventions. While anthropometric indicators based on international standards were regularly used for programme purposes, data on IYCF could not be collected with similar rigor until 2010. In 2009, with support from Alive & Thrive and UNICEF, the NNSS questionnaire was reviewed and additional content incorporated to measure IYCF practices. The tool was pilot‐tested in 10 provinces and revised before nationwide roll‐out in 2010.The tool comprises four pages, the first three of which focus on collecting data relating to maternal nutrition and IYCF. The last page is flexibly designed to incorporate planners' data requests for other relevant activities (e.g. mass media interventions, food security). Once analysed, the data are presented in a report comprising provincial profiles and maps illustrating IYCF practices. Importantly, the IYCF data have been used for policy advocacy (e.g. maternity leave legislation, advertisement law), programme planning, trend monitoring and capacity building. Adoption of the IYCF indicators was successful due to strategic timing, a phased approach, buy‐in from stakeholders and capacity building at all levels to ensure the quality and use of data. Further revisions to the NNSS (e.g. sampling methodology, quality assurance systems) will be important to ensure the reliability of indicators.